Effect of cropping systems and nutrient management practices on growth, productivity, economics and nutrient uptake of soybean (Glycine max) - PRAJAPAT, K; VYAS, A K; DHAR, SHIVA (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during kharif seasons of 2011 and 2012 at the research farm of Indian Agricultural Research Institute, New Delhi to evaluate the performance of soybean [Glycine max (L.) Merril] as affected by 4 soybean-based cropping systems and 5 nutrients management practices. Significantly higher pods/plant and seed yield of soybean were recorded in soybean–wheat (Triticum aestivum L.)–mungbean [Vigna radiata (L.) Wilczek] system compared to soybean–wheat–fallow system. Soybean grown under soybean–wheat–mungbean system had significantly higher total uptake N and K over soybean–wheat–fallow system. Application of 25% RDF + 50% RDN through FYM along with Rhizobium and PSB gave significantly highest pods/plant, seeds/pod and seed and stover yields of soybean over control during both the years of study. Application of 50% RDF + 25% RDN thorough FYM + biofertilizers or 25% RDF + 50% RDN through FYM + biofertilizers, remaining on par with each other fetched maximum net returns. Significantly maximum total uptake of N and P were recorded with the application of 25% RDF + 50% RDN thorough FYM + biofertilizers over control.